Cosmology and Hindu Thought - Balslev, Anindita Niyogi (Zygon, 1990)
Abstract. This paper outlines some major ideas concerning cosmogony and cosmogony and cosmology that pervade the Hindu conceptual world. The basic source for this discussion is the philosophical literature of some of the principal schools of Hindu thought, such as VaiVaiśika, Sānkhya, and Advaita Vedānta, focusing on the themes of cosmology, time, and soteriology. The core of Hindu philosophical thinking regarding these issues is traced back to the Rk Vedic cosmogonical speculations, analyzed, and contrasted with the “views of the opponent.” The relevance of the Hindu worldview for overcoming the conflict between science and religion is pointed out.